Case report: Unruptured sinus of Valsalva aneurysms causing postural angina pectoris and false “pulmonary hypertension” - Zhou, Chi; Tao, Jingwen; Li, Sheng (Frontiers in Cardiovascular Medicine, 2023)
A 37-year-old woman presented with worsening intermittent chest pain and dyspnea in the previous year. Although the dyspnea was exertion-dependent, her chest pain relied heavily on her postural position, worsening in the supine position but being alleviated by lying prone or by sitting up and leaning forward. She was cyanotic, and a diastolic murmur in the left third intercostal space was auscultated. An electrocardiogram recorded when she laid flat and had angina pectoris attacks showed ST-segment elevation in the aVR, depression in the II, III, aVF, and V3-V6 leads. However, when she sat up for a few minutes, her symptoms and ST-segment abnormalities disappeared. Echocardiography and cardiac computed tomography angiography revealed large unruptured aneurysms of the left and non-coronary sinuses, along with a dilated aortic root, severe aortic regurgitation, and right ventricular high pressure. Coronary angiography demonstrated 90% pulsating stenosis of the left main coronary artery and 80% pulsating stenosis of the proximal left circumflex artery, presumably caused by pulsation of the dilated sinus of Valsalva aneurysm under blood pressure. Genetic testing revealed c.1781 C>G nonsense mutations in the FLNA gene. The patient underwent surgery, which confirmed dual unruptured left/non-coronary sinus of Valsalva aneurysms. Our case illustrates an unusual postural form of angina pectoris and false ‘pulmonary hypertension’ caused by a large dual unruptured left/non-coronary sinus of Valsalva aneurysms.